2017
DOI: 10.1515/ctra-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Between Individualism and Collectivism: Perception and Profiles of Creativity in Poland and Japan

Abstract: The aim of the study was to analyze creativity profiles and understanding of creativity in Poland and Japan. The study included 597 participants (233 Polish and 364 Japanese).Qualitative and quantitative analyses were carried out (mixed method). We identified the existence of five different creativity profiles and ten categories for defining creativity, with significant differences in frequency between the two countries. The obtained results are discussed from the perspective of intercultural differences and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Nevertheless, in the context of world cultural clusters, Georgia is believed to be close to the Eastern European cluster ( Tkeshelashvili, 2009 ). Similarly to Eastern European cultures ( Gajda and Oie, 2017 ), Georgian society is becoming more and more Western against the backdrop of globalization. A study of 108 business organizations found individualism largely prevailing ( Jamagidze et al, 2011 ); this is especially true for young working generations that value autonomy ( Sumbadze, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the context of world cultural clusters, Georgia is believed to be close to the Eastern European cluster ( Tkeshelashvili, 2009 ). Similarly to Eastern European cultures ( Gajda and Oie, 2017 ), Georgian society is becoming more and more Western against the backdrop of globalization. A study of 108 business organizations found individualism largely prevailing ( Jamagidze et al, 2011 ); this is especially true for young working generations that value autonomy ( Sumbadze, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the USA is a highly individualistic culture, with a score of 91 on individualism, whereas Poland scores 60 on this dimension (Hofstede Insights, 2020). Poland represents a combination of individualistic and collectivistic values as a result of over 40 years of being subjected to communist rule of the USSR and predominance of Catholic Church, with an implementation of Western values after the end of communism in the 1980s (Gajda & Oie, 2017). In recent years, Poland has shifted somewhat toward individualism (Bartosik‐Purgat & Schroeder, 2007; Gajda & Oie, 2017).…”
Section: Marital and Intimate Relationship Contexts In Poland And The Usamentioning
confidence: 99%
“…Poland represents a combination of individualistic and collectivistic values as a result of over 40 years of being subjected to communist rule of the USSR and predominance of Catholic Church, with an implementation of Western values after the end of communism in the 1980s (Gajda & Oie, 2017). In recent years, Poland has shifted somewhat toward individualism (Bartosik‐Purgat & Schroeder, 2007; Gajda & Oie, 2017). Second, Polish society endorses traditional notions of adulthood that include heterosexual marriage and having children, a general disapproval and low incidence of divorce, and less approval for alternative family and marital forms (e.g.…”
Section: Marital and Intimate Relationship Contexts In Poland And The Usamentioning
confidence: 99%
“…In Gajda & Oie (2017) study, they aimed to investigate the creativity profiles between two cultures which were Poland and Japan. The researchers quoted that according to Hofstede (1983), Japan is considered as a collectivist culture which is similar to other Eastern culture such as South Korean (Jang et al, 2019) which emphasize on cooperation, duty and compromise with the group while Poland, one of the Western countries is more dominated by individualistic value (Hofstede, 1983 as cited in Gajda et al, 2017). 597 participants were recruited among students from two universities in Warsaw and two Tokyo universities respectively which consisted of 230 Polish and 364 Japanese participants.…”
Section: Creativity's View From Different Culturesmentioning
confidence: 99%
“…The results show that Polish students indicate independence when presenting creativity while Japanese groups show lower independence in creativity presentation. Gajda et al (2017) explained that the Japanese function differently compared to European realities as they are more elaborated, depends on the team, and build an effective team as their goal that works well apart from crafting new products (Ahmadi Faqih et al, 2018;Herbig & Jacobs, 1996as cited in Gajda, 2017. However, some Japanese participants show that rather than making a revolutionary change, they exhibit higher cognitive curiosity, a great interest in acquiring knowledge, and the willingness to learn from traditional skills and customs despite having low creativity ability (Lubart, 1999;Mito, 2015as cited in Gajda, 2017.…”
Section: Creativity's View From Different Culturesmentioning
confidence: 99%